Incidence of outflow tract ventricular tachycardia long after surgical aortic valve replacement. Issue 2 (19th January 2021) - Goto, Kentaro; Ono, Yuichi; Osaka, Yuki; Nomoto, Hidetsugu; Miyazaki, Toru; Suzuki, Asami; Kurihara, Ken; Someya, Takeshi; Takahashi, Yoshihide; Otomo, Kenichiro; Goya, Masahiko; Sasano, Tetsuo
Abstract: Background: The peri‐outflow tract region could be the origin of ventricular tachycardia (VT) after aortic valve replacement (AVR). However, the clinical characteristics of outflow tract ventricular tachycardias (OTVTs) after AVR are yet to be clarified. This study investigated the incidence, risk factors, and clinical characteristics of patients with OTVTs after AVR. Methods: We retrospectively analyzed the clinical course of 120 patients who had undergone surgical AVR (SAVR) between April 1980 and October 2018. The patients had no ischemic or diagnosed cardiomyopathies other than primary aortic valve diseases. Results: Six patients (5.0%) developed OTVTs after SAVR. The average onset was at 10.8 ± 5.7 years after SAVR. All cases of VT arose from the inferior axis and included left and right bundle branch block configuration. Two patients who underwent cardiac magnetic resonance imaging (MRI) had late gadolinium enhancement (LGE) in the midlayer of the left ventricle basal anteroseptal wall. Patients with periaortic VTs had significantly larger left ventricular (LV) diameter at systole, lower LV ejection fraction, higher positive rates of signal‐averaged electrocardiogram (SAECG), and nonsustained VTs on Holter monitoring. On ablation, local fragmented potentials with low voltage zones were observed in accordance with the LGE distribution. Multiple VTs originating from the periaortic region were provoked in the sessions. Conclusions: Acute OTVT was found in 5% of patients after SAVR. Arrhythmia risk stratification by SAECG, Holter ECG, and cardiac MRI should be considered for a long period in patients after SAVR. Abstract : Based on our results, acute onset of OTVT was found in 5% of patients who received SAVR. Therefore, we suggest that arrhythmic risk stratification should be considered for patients who have undergone SAVR for a long period.